2002
DOI: 10.12938/bifidus1996.21.21
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Bone of Stimulated Intestinal Mineral Absorption Following Fructooligosaccharide Consumption in Rats

Abstract: Several studies have been carried out to establish the role of calcium and magnesium in bone. These minerals may play an important role in bone structure or strength. Fructooligosaccharides (FOS) are known to be stimulators of intestinal mineral absorption. In intact rats, bone volume and the mineral content (Ca, and Mg ) of the bone surface are greater in FOS-fed rats. Moreover, a significant relationship exists between the absorption of these minerals and their content in bone. Osteopenia is known to follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The odds ratios in the various age groups for reporting hip fractures related to a low vs. high frequency of using cheese were: age 30 years (yes/no=43/3927), OR=2.43, 95% CI=1. 16 Crude mean frequency of cheese use in the various age groups in subjects reporting hip fractures and 'controls' is shown in Figure 4. There was an age related increase in the frequency of cheese intake, and cheese was more frequently used in 'controls' than in hip fracture cases (except in age group 75-76 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The odds ratios in the various age groups for reporting hip fractures related to a low vs. high frequency of using cheese were: age 30 years (yes/no=43/3927), OR=2.43, 95% CI=1. 16 Crude mean frequency of cheese use in the various age groups in subjects reporting hip fractures and 'controls' is shown in Figure 4. There was an age related increase in the frequency of cheese intake, and cheese was more frequently used in 'controls' than in hip fracture cases (except in age group 75-76 years).…”
Section: Resultsmentioning
confidence: 99%
“…In the rat, indigestible carbohydrates of plants, such as fructooligosaccarides, have been shown to increase intestinal calcium absorption, calcium balance, and bone mineral density (16,17). Among mechanisms of action are increased absorptive area of the large bowel produced by a high fibre content, and formation of short-chain fatty acids serving to promote calcium absorption in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, indigestible carbohydrates of plants, such as fructo-oligo-saccarides, have been shown to increase intestinal calcium absorption, calcium balance, and bone mineral density [ 15 , 16 ]. Among mechanisms of action are increased absorption area of the large bowel produced by a high fibre content and formation of short-chain fatty acids which could promote calcium absorption in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of prebiotic-mediated improvements in mineral uptake remain unclear, but fermentative activities of the microbiota, including the production of SCFA and reductions in luminal pH, are believed to be involved in improving mineral solubility and extending the site of mineral absorption further into the colon (Morohashi, 2002) (Figure 5.11). In rat studies, increased calcium uptake has lead to improved bone mineralization for animals fed GOSs (Chonan et al, 1995) or lactulose (Mizota, 1996), and improved calcium uptake has also been reported in human feeding studies using these two lactose derivatives (Van den Heuvel et al, 1999;2000).…”
Section: Mineral Absorptionmentioning
confidence: 99%